A global relation of fire smoke re-circulation behaviour in urban street canyons - Hu, Longhua; Zhang, Xiaochun; Zhu, Wei; Ning, Zhi; Tang, Fei (Journal of Civil Engineering and Management, 2015)
Street canyon, formed by buildings along two sides of a road, is an important and ubiquitous architectural element in the metropolises. When a fire occurs in an urban street canyon, a critical serious phenomenon is found to happen where the uprising fire smoke is re-circulated back into the base of the street canyon by the wind flow beyond a critical velocity. Theoretical analysis is derived based on Froude number (Fr), by balancing the inertial force of the wind flow to the buoyancy strength of the fire smoke. It is found that the critical re-circulation wind velocity is proportional to an integrated global parameter . Large Eddy Simulations (LES) are carried out by Fire Dynamics Simulator (FDS). The critical Froude number (Fr) is found to be about 0.7~0.8. The simulation results are well collapsed by the generalized theoretical relation. It is further revealed that the non-dimensional critical re-circulation wind velocity . against aspect ratio of street canyons in the skimming flow pattern (W/H < 1.43) falls into two behavioural regimes, where it firstly increases then remains constant with the increase in street canyon aspect ratio (W/H) with a turning point at W/H = 1. A global non-dimensional relation is finally achieved for the critical re-circulation wind velocity (u), fire heat release rate (Q) and its height (H) to the top of the street canyon as well as the street canyon aspect ratio (W/H).